Developments in CO2 Compression and Purification Unit (CPU) for Oxy-fuel Combustion Power Plant - Yan Yan, Harry (Cranfield University, 2018)
Poster presented at the Cranfield Doctoral Network Annual Event 2018.Developments in Carbon Dioxide Compression and Purication Unit (CPU) for Oxyfuel Combustion Power Plant. Oxyfuel combustion technology as one of three major carbon capture technologies, which has been largely investigated from bench scale to demonstration scale. The difference of carbon dioxide gas quality in oxyfuel combustion technology which require additional process with high cost and energy penalty than that of pre- and post-combustion capture technology. In this work, previous work from the oxyfuel combustion demonstration projects and industrial technologies of CPU led by Air Products, Air Liquide, Linde and Praxair have been reviewed. A novel concept that using wet ozone direct oxidation absorption for simultaneous removal SOx and NOx for CPU has been proposed and validated in Aspen Plus. The results indicated that 99% NO, 90% NO2 and nearly 100% of SO2 was removed at pH 11 before compression and the purity of product CO2 can achieve 99.7%. Comparison with the previous technologies, this method achieve high purity of product CO2 with simplified process and can realize the negative emission in oxyfuel combustion power plant.
Keywords: 'CCS'; 'CO2 compression'; 'gas cleaning'; 'CranfieldDN2018'; 'Power and Energy Systems Engineering (excl. Renewable Power)'